Guidelines for safe process operations and maintenance. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1995)
First-line managers have to maintain the integrity of facilities, control manufacturing processes, and handle unusual or emergency situations, as well as respond to the pressures of production demand. On a daily basis, they are closest to the operating personnel who may be injured by a process accident, and they are in the best position to spot problem conditions and to act to contain them. This book offers these managers "how-to" information on process safety management program execution in the operations and maintenance departments, recommending technical and administrative process.
Keywords: Chemical engineering -- Safety measures.; elektronické knihy; electronic books